2007
DOI: 10.1021/jp076576t
|View full text |Cite
|
Sign up to set email alerts
|

Cyclodextrin-Based Self-Assembled Nanotubes at the Water/Air Interface

Abstract: Native alpha-cyclodextrin (alpha-CD) is found to spontaneously form films at aqueous solution/air interfaces. Shape-response measurements to volume perturbations on drops hanging from a capillary indicate that temperature and sodium dodecyl sulfate (SDS) concentration strongly modify the viscoelastic properties of such films. By using isothermal titration calorimetry (ITC), Brewster angle microscopy (BAM), atomic force microscopy (AFM), and molecular dynamics (MD) simulations, it is shown that the films consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
60
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(67 citation statements)
references
References 16 publications
7
60
0
Order By: Relevance
“…The study of CD nanotubes has been paid much attention, and most of the CD nanotubes were found to be induced by organic molecules, which has become a subject of great interest [9][10][11][12][13][14][15][16][17]. Interestingly, Agbaria and Gill reported that some oxazole molecules including 2-phenyl-5-(4-diphenylyl) 1,3,4-oxadiazole (PBD) could form inclusion complexes with c-CD at lower concentrations, which could further form extended nanotubes at relatively high concentrations [2,12].…”
Section: Introductionmentioning
confidence: 99%
“…The study of CD nanotubes has been paid much attention, and most of the CD nanotubes were found to be induced by organic molecules, which has become a subject of great interest [9][10][11][12][13][14][15][16][17]. Interestingly, Agbaria and Gill reported that some oxazole molecules including 2-phenyl-5-(4-diphenylyl) 1,3,4-oxadiazole (PBD) could form inclusion complexes with c-CD at lower concentrations, which could further form extended nanotubes at relatively high concentrations [2,12].…”
Section: Introductionmentioning
confidence: 99%
“…The type of molecules that can be introduced in the cavity to form an inclusion complex, depends mainly on geometric factors rather than on chemical properties, however these are evidently not the only factors, it is shown that the ability of CDs to form supramolecular assemblies is also due to the effect of conformational adaptation of the host and the guest molecules. In some cases the CD hardly modifies his atomic positions by the inclusion complex formation [3,4], but there are some compounds capable of changing the truncated cone shaped structure of CDs to nanocylinder-like blocks [5,6]. The present work considers the CD cavity like a conical geometry, to take into account these structural changes it could be applied the characteristics of a continuum model for the interaction energy of a cylindrical structure for CDs studied in previous work [7].…”
Section: Introductionmentioning
confidence: 99%
“…A large number of novel, ordered supramolecular materials [1][2][3] as well as rotaxane [4], polyrotaxane [5], catenane [6], molecular necklaces [7] and other supramolecular assemblies have been constructed. Among all of these, the study of CD nanotubes has attracted great attention [8][9][10].…”
Section: Introductionmentioning
confidence: 99%